Experimental Investigation of Fluid Flow and Heat Transfer in Microchannels - Sharma, Rajesh; Singh, Balkar; Jadon, Vijay Kumar (Asian Journal of Engineering and Applied Technology, 2013)
An experimental investigation was conducted to explore the characteristics of fluid flow and heat transfer in rectangular microchannels using water as a working fluid in single-phase flow. The micro channels considered having width of 350 microns; with the channel depth 2.5 mm. Test piece was made of copper and contained twenty three microchannels in parallel. The experiments were conducted with water, with the Reynolds number ranging from 375 to 2000. Numerical predictions obtained based on a classical, continuum approach were found to be in good agreement with the experimental data, suggesting that a conventional analysis approach can be employed in predicting heat transfer behavior in microchannels of the dimensions considered in this study.